E- Formative Assessment Integration in Collaborative Inquiry: A Strategy to Enhance Students' Conceptual Understanding in Static Fluid Concepts - Kusairi, S.; Hardiana, H. A.; Swasono, P.; Suryadi, A.; Afrieni, Y. (Jurnal Pendidikan Fisika Indonesia, 2021)
This study aims to analyze students' conceptual Ã‚Â understanding and their difficulties in grasping the static fluid concepts after they learned throughout integrated e-formative assessments in collaborative inquiry. This mixed-method research involved 28 senior high school students.Ã‚Â  Students studied static fluid concepts with a collaborative inquiry strategy supported by the implementation of web-based formative assessment. Students' conceptual understanding and their difficulties were assessed using multiple-choice questions with the reasons (r= 0.75.). The result showed that students' conceptual understanding was improved after learning, which is indicated by the moderate normalized gain value (0.5374), and the strong effect size (2.772). However, there were still some difficulties that students have regarding factors that influence buoyancy. Providing more portion of the conceptual discussions and practising problem-solving during learning through e-formative assessment were recommended. Learning difficulties that have been found in this study can be considered and anticipated by teachers in teaching static fluid topic.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â